Investigating how South African humanities researchers engage with digital archives - Mtombeni, Khanyisa (Department of Computer Science, 2022)
OBJECTIVE: Despite technological developments in the Digital Humanities space, it is unclear that the facilities offered by digital archives support the needs of Humanities researchers in developing countries. The purpose of this thesis is to investigate how South African Humanities scholars use digital archives in their research as well as in teaching and other academic activities. METHODS: This thesis utilizes non-random convenience sampling. A feature determination study provided the sampling frame, defined the scope for the survey tool, and was used to uncover trends in digital archives development in South Africa. A self-administered online survey was conducted with Humanities researchers in South Africa to answer the research question. The thesis utilises basic descriptive statistics in its attempt to study and interpret the responses of participating researchers. RESULTS: 102 participants responded to the online survey. Despite many South African digital archives having the functionality to discover, browse and search collections, they are missing the features for collaboration, accessing and managing resources. Only 20% of the survey respondents are satisfied with South African digital archives' process of making content easy to find and accessible, whereas 48% of the respondents consider themselves users of complex digital resources, 44% have the knowledge and experience for using Digital Humanities tools and services, and more than 70% find technology to be useful for learning and teaching. CONCLUSIONS: The usage of archives and their functionalities vary widely. Users have stronger preferences for tools that support basic discovery and personal and collaborative research, but many consider existing support for basic features to be inadequate. In terms of advanced functionalities for managing digital resources, users are interested in these to varying levels, but the inadequate support means that these are still somewhat speculative.